2015
DOI: 10.1055/s-0035-1549920
|View full text |Cite
|
Sign up to set email alerts
|

Fasted Exercise and Increased Dietary Protein Reduces Body Fat and Improves Strength in Jockeys

Abstract: The present study assessed the effects of a diet and exercise intervention in jockeys on body composition, metabolism, bone and mental health. 10 jockeys followed an individually prescribed 6-wk diet (Carbohydrate=2.5-3.5 g/kg, Protein=2.5 g/kg, Fat=1.0 g/kg). Body mass (59.2±4.6 vs. 57.6±4.5 kg), fat mass (7.5±3.5 vs. 6.2±2.6) and body fat (13.1±5.9 vs. 11.5±4.9%) all decreased (P<0.05) from pre to post-intervention whilst lean mass (47.1±5.3 vs. 47.0±5.5 kg) was maintained (P=0.80). RMR (1703±329 vs. 1975±31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 38 publications
4
33
0
Order By: Relevance
“…Pasiakos et al 2013; Morton et al 2018;Longland et al, 2016;Wilson et al, 2013;Wilson et al, 2015). Nonetheless, we acknowledge the potential under-reporting associated with the dietary assessment measures utilised here (i.e.…”
mentioning
confidence: 89%
“…Pasiakos et al 2013; Morton et al 2018;Longland et al, 2016;Wilson et al, 2013;Wilson et al, 2015). Nonetheless, we acknowledge the potential under-reporting associated with the dietary assessment measures utilised here (i.e.…”
mentioning
confidence: 89%
“…Referring back to the interviewees via member checking upon transcription and interpretation of themes similarly helped achieve a good standard of trustworthiness of the data. Alternative to seeking external modes of validation, the lead researcher consistently upheld a level of self-reflexivity and critical thinking throughout the duration of the study, contemplating his own views and ideologies to evidence sincerity in the process.The relevance, timing and significance of this topic in context of the horseracing industry and outcomes of previous quantitative enquiry(Dolan et al, 2011(Dolan et al, , 2012Wilson et al, 2012Wilson et al, , 2013Wilson et al, , 2014Wilson et al, , 2015) makes the present research a worthy topic.…”
mentioning
confidence: 89%
“…The interview was centred on seeking the perceptions and thoughts of current weight-making practices in jockeys, how they identify jockeys in relation to other elite weight-making sportspeople, and their opinions of current race-day food provision at racetracks. Questions were devised with the outcomes of previous literature in mind (Dolan et al, 2011;Greene et al, 2013;Wilson et al, 2012;Wilson et al, 2013;Wilson et al, 2015) as well as the research group's own ideas in capturing the necessary responses to achieve the study aims.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the aforementioned practices, we have recently shown that jockeys can make weight safely (Wilson et al, 2012;Wilson, Pritchard, et al, 2015) through the implementation of a structured dietary and exercise strategy. However, to provide individually tailored nutritional strategies for jockeys, it is essential to accurately calculate the daily total energy expenditure (TEE).…”
Section: Introductionmentioning
confidence: 99%